Assessing the Political Stability of Oman - Katz, Mark N. (2004)
Oman is facing important economic and political challenges. The economic challenge it faces is that its population is rising while its oil reserves are declining. The political challenges it faces are the extreme concentration of authority in the hands of one man (Sultan Qaboos), the sultan's unwillingness to allow meaningful political participation or dialogue, political legitimacy issues concerning both Sultan Qaboos and the succession process he has set up, and sporadic but persistent signs of opposition. This article examines these problems and assesses their implications for the political stability of Oman.
Keywords: Vie politique -- Oman -- 1970-2020

Durūs min Musnad al-Rabīʿ wa-Mudawwanat Abī Ghānim. Part 1: fī Fiqh al-Ṣalāt. Part 2: fī Fiqh al-Ṣalāt. Part 3: fī Fiqh Ādāb Qaḍā’ al-Ḥāja. Part 4: maʿa Fuqahā’ al-Madrasa al-Jābiriyya - Wahībī, Khālid b. Mubārak al- (2004)
Keywords: Fiqh -- Libye -- 8e siècle

al-Jarḥ wa’l-Taʿdīl. Qirā’a fī Turāth al-Madrasa al-Jābiriyya - Wahībī, Khālid b. Mubārak al- (2004)